Reformulasi Tafsir: Studi Pemikiran Gender Asghar Ali Engineer - Abdul Rasyid Ridho (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
Asghar Ali Engineer is one of the figures who promotes and implements liberation theology. Liberation theology emphasizes praxis rather than metaphysical theoritization which includes abstract and ambiguous concepts. The praxis in question is of a liberal nature and involves dialectical attraction between "what is" and "what should be". As well as this ambiguous meaning that opens opportunities for flexibility in making creative and constructive changes. This theology is applied, among others, related to the injustice towards women. Women realize that they have not really been 'individualized', have not been treated as whole human beings. This condition is of course felt as a confinement that shackles women. So from a normative perspective, it is clear that the Koran upholds the principle of equality between men and women. In other words, the Qur'an is very concerned with issues of gender equality. However, when viewed from a contextual perspective, the al-Qur'an sometimes places men one level above women.